Management Rights in Underground Post Application of Law Number 11 of 2020 Concerning Copyright and Implementation Regulations - Karina, Ida Ayu Aditya; Koeswahyono, Imam; Anggraini, Erna (Budapest International Research and Critics University, 2021)
This thesis is entitled